(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Since the colonial period, the relationship between education and federalism has evolved. In 1917, the Sadler Commission declared education a state subject, assigning significant coordinating responsibilities to the central government. After India gained independence, the constitution-makers continued to delegate authority over education to state governments. However, the 42nd Amendment, in a substantial departure from the fundamental constitutional separation of powers, transferred education to the Concurrent List. This move made education a "joint duty," with the Union and the states becoming "equal partners." Nevertheless, the enactment of the National Policy on Education (NPE) in 1986 continued the trend toward centralization in education. Under the leadership of Prime Minister Narendra Modi, the Union Cabinet adopted the new National Education Policy (NEP) on July 30th, 2020, paving the way for wide-ranging changes in the educational sector across the country. The 34-year-old National Policy on Education (NPE) was replaced, aiming to make the present education system comprehensive, adaptable, and interdisciplinary for future generations. However, introducing the new education policy and related programs in the states is a concern, as it has only been initiated in a handful of states. In most of these states, the ruling party's government is at the center. The central problem addressed in this research article is the implementation of NEP 2020 in the Indian federal state and its impact on India's cooperative federalism. These are some of the main points raised by experts and educationists who oppose NEP 2020. They argue that a nationalized education policy will not work in a diverse country like India. States ruled by opposition parties face many hurdles and opponents in implementing the new education policy. In such a situation, the diplomatic skills of the central government can prove decisive in pursuing this policy, which aims to decentralize the authority of states to make rules on education and promote cooperative federalism."